Prospective neonatal screening for severe T‐ and B‐lymphocyte deficiencies in Seville. Issue 1 (23rd November 2015) - de Felipe, Beatriz; Olbrich, Peter; Lucenas, José Manuel; Delgado‐Pecellin, Carmen; Pavon‐Delgado, Antonio; Marquez, Josefina; Salamanca, Carmen; Soler‐Palacin, Pere; Gonzalez‐Granado, Luis Ignacio; Antolin, Laura Ferreras; Borte, Stephan; Neth, Olaf
Abstract: Background: Early diagnosis of primary immunodeficiency such as severe combined immunodeficiency (SCID) and X‐linked agammaglobulinemia (XLA) improves outcome of affected children. T‐cell‐receptor‐excision circles (TRECs) and kappa‐deleting‐recombination‐excision circles (KRECs) determination from dried blood spots (DBS) identify neonates with severe T‐ and/or B‐lymphopenia. No prospective data exist of the impact of gestational age (GA) and birth weight (BW) on TRECs and KRECs values. Methods: TRECs and KRECs determination using triplex RT‐PCR (TRECS‐KRECS‐β‐actin‐Assay) from prospectively collected DBS between 02/2014 and 02/2015 in three hospitals in Seville, Spain. Cut‐off levels were TRECs < 6/punch, KRECs < 4/punch and ‐β‐actin>700/punch. Internal (SCID, XLA, ataxia telangiectasia) and external controls (NBS quality assurance program, CDC) were included. Results: A total of 5160 DBS were tested. Re‐punch was needed in 77 samples (1.5%) due to insufficient β‐actin (<700 copies/punch). Pre‐term neonates (GA<37 weeks) and neonates with a BW<2500 g showed significantly lower TRECs and KRECs levels (p < 0.001). Due to repeat positive results five neonates were re‐called (<0.1%): Fatal chromosomopathy (n = 1; TRECs 1/KRECs 4); extreme pre‐maturity (n = 2; TRECs 0/KRECs 0 and TRECs 1/KRECs 20 copies/punch); neonates born to mothers receiving azathioprine during pregnancy (n = 2; TRECs 92/KRECs 1 and TRECs 154/KRECs 3 copies/punch). All internal and external controls were correctly identified. Conclusions: TRECS‐KRECS–β‐actin‐Assay correctly identifies T‐ and B‐cell lymphopenias. Pre‐maturity and low BW is associated with lower TREC and KREC levels. Extreme pre‐maturity and maternal immune suppressive therapy may be a cause for false positive results of TRECs and KRECs values, respectively. To reduce the rate of insufficient samples, DBS extraction and storage need to be improved. Abstract :